Disability stereotyping is shaped by stigma characteristics - Granjon, Marine; Rohmer, Odile; Popa-Roch, Maria; Aubé, Benoite; Sanrey, Camille (Group processes & intergroup relations, 2024)
The literature suggests that people with invisible disabilities face more social difficulties than those with visible ones. Thus, the visibility criterion can constitute a core factor to understand the stigmatisation of people with disabilities. The main aim of this research is to examine if the “warm but incompetent” stereotype associated with disability varies according to the visibility criterion. A complementary aim is to investigate how taking onset controllability into account can help to understand the stereotyping faced by people with a disability. To do this, we conducted four studies, using between- (pilot study) and within-subject (Studies 1a, 1b, and 2) designs. Our results consistently support the hypothesis that stereotypes associated with disabilities vary according to visibility. Specifically, people with invisible disabilities are perceived to be less warm but more competent than those with visible disabilities. Furthermore, more surprisingly, perceived controllability increases both warmth and competence perceptions. These findings highlight the importance of considering the characteristics of a disability to understand stigmatisation.